AN ANALYSIS OF TERM SARIYYAH IN THE TRANSLATION OF THE BOOK TITLED NURUL YAQIN FI SIRAH SAYYIDIL MURSALIN (2010) BY SHEIKH MUHAMMAD AL-KHUDHARIY - Syahrefi, Namira Fauzia; Muta'ali, Abdul (Arabi : Journal of Arabic Studies, 2021)
This paper presents the analysis of the translation of the term sariyyah in the book "Nurul Yaqin Fi Sirah Sayyidil Mursalin” by Sheikh Muhammad Al-Khudhari. The translator of this book does not translate the term sariyyah. This translating process is called foreignization, the opposite of localization. The data was taken from the book "Nurul Yaqin Fi Sirah Sayyidil Mursalin” by Sheikh Muhammad Al-Khudhari which was published by Dar El Hadits, Cairo in 2010, with a total of 270 pages and its Indonesian translation book entitled "Nurul Yaqin Sirah Nabi Muhamad Pemimpin Para Rasul” (Nurul Yaqin The Biography of Muhammad PBUH, Leader of the Apostles). The word sariyyah is repeated 45 times in the Arabic book and 46 times in the Indonesian translated book. The researcher used the descriptive analysis method with the Peter New Mark translation procedure approach using the V diagram translation theory. The analysis results prove that the word sariyyah is not translated because the translator is doubtful about the appropriate sariyyah word matching in Indonesian.